Burley Tobacco Clubs in Malawi : Nonmarket Institutions for Exports - Negri, Mariano; Porto, Guido G. (World Bank, Washington, DC, 2012)
This paper studies nonmarket institutions that facilitate exports. In Malawi, as in many other developing countries, farmers face numerous constraints that disconnect them from export markets. The paper explores the role of a local institution, the burley tobacco clubs, in bridging smallholders to exports. Burley clubs potentially enable farmers to increase their tobacco farming productivity by providing services related to institutional access, collective action, economies of scale, and supporting network. Using matching methods and instrumental variable techniques, the authors find that tobacco club membership causes an increase of between 40-74 percent in output per acre and an increase of between 45-89 percent in tobacco sales per acre. Instead, neither the land share allocated to tobacco nor the unit value obtained by the producers is affected by club membership.